2019
DOI: 10.1080/07347324.2019.1669513
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect Relationship between Interpersonal Trauma History and Alcohol Use via Negative Cognitions in a Multisite Alcohol Treatment Sample

Abstract: Although interpersonal trauma history (ITH) is frequently associated with alcohol use disorder (AUD), little is known about specific psychological constructs that may indirectly link these phenomena. This study hypothesized that one such construct may be negative cognitive schemas that often emerge in the aftermath of trauma. Secondary latent variable modeling was conducted using the Project MATCH sample of adults receiving treatment for AUD (N = 1726; 24.3% women; 38.63% ITH). The negative cognitions latent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies have shown that posttraumatic cognitions mediate the association between PTSD symptoms and alcohol outcomes in community and college samples. Fokas and colleagues (2020) found that an observed positive association between assault and alcohol use was partially explained by the presence of negative cognitions. Thompson and Kingree (2010) found that the association between sexual victimization and alcohol problems was influenced by the presence of negative cognitions.…”
mentioning
confidence: 99%
“…Several studies have shown that posttraumatic cognitions mediate the association between PTSD symptoms and alcohol outcomes in community and college samples. Fokas and colleagues (2020) found that an observed positive association between assault and alcohol use was partially explained by the presence of negative cognitions. Thompson and Kingree (2010) found that the association between sexual victimization and alcohol problems was influenced by the presence of negative cognitions.…”
mentioning
confidence: 99%